Загальний пiдхiд для опису класичних рiдинних систем i ядерної матерiї - Cherevko, K. V.; Jenkovszky, L. L.; Sysoev, V. M.; Zhang, Feng-Shou (Publishing house "Academperiodika", 2019)
This work is an attempt to give a brief overview of the implementation of the statistical thermodynamics to hadronic matter. The possibility to use the hydrodynamic approach for developing the physical model of the formation of exotic structures in the head-on intermediate-energy heavy ion collisions is discussed. That approach is shown to be able to provide simple analytical expressions describing each step of the collision process. This allows for extracting the data concerning nuclear matter properties (surface tension, compressibility, etc.) from the properties of observed fragments. The advantages of the thermodynamic analysis of phase trajectories of the system in heavy ion collisions are discussed. Within the thermodynamic approach, the method to evaluate the curvature correction to the surface tension from the nuclear matter equation of state is described. The possibility to use statistical thermodynamics in the studies of hadronic matter and quantum liquids is discussed.